Assessment of Suitable Reference Genes for Quantitative Gene Expression Studies in Melon Fruits - Kong, Qiusheng; Gao, Lingyun; Cao, Lei; Liu, Yue; Saba, Hameed; Huang, Yuan; Bie, Zhilong (Frontiers in Plant Science, 2016)
Melon (Cucumis melo L.) is an attractive model plant for investigating fruit development because of its morphological, physiological, and biochemical diversity. Quantification of gene expression by quantitative reverse transcription polymerase chain reaction (qRT-PCR) with stably expressed reference genes for normalization can effectively elucidate the biological functions of genes that regulate fruit development. However, the reference genes for data normalization in melon fruits have not yet been systematically validated. This study aims to assess the suitability of 20 genes for their potential use as reference genes in melon fruits. Expression variations of these genes were measured in 24 samples that represented different developmental stages of fertilized and parthenocarpic melon fruits by qRT-PCR analysis. GeNorm identified ribosomal protein L (CmRPL) and cytosolic ribosomal protein S15 (CmRPS15) as the best pair of reference genes, and as many as five genes including CmRPL, CmRPS15, TIP41-like family protein (CmTIP41), cyclophilin ROC7 (CmCYP7), and ADP ribosylation factor 1 (CmADP) were required for more reliable normalization. NormFinder ranked CmRPS15 as the best single reference gene, and RAN GTPase gene family (CmRAN) and TATA-box binding protein (CmTBP2) as the best combination of reference genes in melon fruits. Their effectiveness was further validated by parallel analyses on the activities of soluble acid invertase and sucrose phosphate synthase, and expression profiles of their respective encoding genes CmAIN2 and CmSPS1, as well as sucrose contents during melon fruit ripening. The validated reference genes will help to improve the accuracy of gene expression studies in melon fruits.